Wideband bandpass filters with reconfigurable bandwidth and fixed notch bands based on terminated cross‐shaped resonator. Issue 6 (14th March 2019) - Bi, Xiao‐Kun; Teng, Cheng; Cheong, Pedro; Ho, Sut‐Kam; Tam, Kam‐Weng
Abstract : In this study, a series of wideband bandpass filters (BPFs) with reconfigurable bandwidth and two fixed notch bands are presented. The fundamental topology is based on a new terminated cross‐shaped resonator (TCSR), which has three poles and four zeros. With the assistance of two symmetrical parallel coupled‐lines, another four poles and two zeros are introduced. As such, a notched‐band bandpass filter with multiple transmission poles and zeros are achieved. To realise the reconfigurable bandwidth, four PIN diodes are used. By controlling the status (switching on/off) of these PIN diodes, three reconfigurable‐bandwidth states can be implemented while the notch bands and centre frequency are maintained unaltered. Meanwhile, it is also found that the lower bandwidth edge of the proposed filter can be independently reconfigurable by inserting a capacitor into the lower stub of the novel TCSR, while the notch bands are kept unchanged. For validation, three prototypes are designed, fabricated, and measured. The measured results agree well with theoretical analysis and therefore verify the simple designing approach of reconfigurable BPFs.